Organization of the stationary seismological observations point - О. З. Ганієв; Т.А. Амашукелі; Л. В. Фарфуляк; К. В. Петренко (Геофизический журнал, 2021)
The Institute of Geophysics of the NASU organizes and carries out continuous regional and local seismic observations on the territory of Ukraine. The article presents a universal modern model of seismic activity monitoring process, which is used in most international seismological agencies (USGS, EMSC, NEIC) and describes a typical stationary point of seismological observations of the National Seismological Network of the Institute of Geophysics of NAS of Ukraine. Seismological network of observations is a complex of systems consisting of stationary seismological points of registration of seismic waves, the distributed system of transfer and collecting of the seismological information, and also the center of operative processing of the data arriving from data registration points. The process of conducting regime seismological observations of local and remote seismic events on the territory of Ukraine and adjacent regions is described. Some important aspects of the need for comprehensive processing of registered events to identify local earthquakes and assess the current activity of tectonic structures in Ukraine are presented.